2021
DOI: 10.1016/j.heliyon.2021.e06667
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prevalence of trypanosomosis, Glossina density and infection along the escarpment of Omo River, Loma district, southern Ethiopia

Abstract: Background The temporal information of trypanosomosis and tsetse apparent density is very limited in the southern part of the country. So, the study was conducted to estimate the temporal, dry and wet seasons, prevalence of cattle trypanosomosis, and tsetse fly apparent density and its infection by trypanosome along the escarpment of Omo River, Loma district, Southern Ethiopia. Methods A total of 964 cattle (482 in each seasons) were examined for trypanosomosis using bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…Two species of trypanosomes were identified in the current study areas, namely, T. congolense (68.85%) and T. vivax (31.15%). This study has confirmed the observation of ( 8 , 13 , 16 , 17 , 49 ) in different parts of Ethiopia. The relatively higher predominance of T. congolense infection in cattle suggests the increased contact of cattle with the savanna tsetse flies, particularly G. pallidipes , which are more efficient transmitters of T. congolense than T. vivax in East Africa ( 12 , 50 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Two species of trypanosomes were identified in the current study areas, namely, T. congolense (68.85%) and T. vivax (31.15%). This study has confirmed the observation of ( 8 , 13 , 16 , 17 , 49 ) in different parts of Ethiopia. The relatively higher predominance of T. congolense infection in cattle suggests the increased contact of cattle with the savanna tsetse flies, particularly G. pallidipes , which are more efficient transmitters of T. congolense than T. vivax in East Africa ( 12 , 50 ).…”
Section: Discussionsupporting
confidence: 90%
“…Trypanosome parasites detected in the mouthpart only were considered in the group of Duttonella ( T. vivax ), those detected both in the mouthparts and midguts were Nanomonas ( T. congolense ), and those found in the midgut, salivary glands, and mouthparts were considered as Trypanozoon ( T. brucei ) ( 17 , 23 , 38 ). Immature infections considered when the trypanosome parasites were detected only in the midgut of the tsetse flies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations